ответ:
[tex]\displaystyle 1)\frac{27}{2}=13\frac{1}{2}=13,5\\ \\2)-\frac{60}{11}=-5\frac{5}{11}[/tex]
решение:
[tex]\displaystyle 1)-6(2x+7)+3(5x-9)=12-3x\\-12x-42+3(5x-9)=12-3x\\-12x-42+15x-27=12-3x\\3x-42-27=12-3x\\3x-69=12-3x\\3x-69+3x=12\\3x+3x=12+69\\6x=12+69\\6x=81\\\\x=\frac{27}{2}=13\frac{1}{2}=13,5\\[/tex]
[tex]\displaystyle 2)2\frac{1}{4}(\frac{2}{3}p-1\frac{1}{3})=3+2\frac{3}{5}p\\ \\\frac{9}{4}(\frac{2}{3}p-1\frac{1}{3})=3+2\frac{3}{5}p\\ \\\frac{9}{4}(\frac{2}{3}p-\frac{4}{3})=3+2\frac{3}{5}p\\ \\\frac{9}{4}(\frac{2}{3}p-\frac{4}{3})=3+\frac{13}5}p\\ \\\frac{3}{2}p-3=3+\frac{13}{5}p\\ \\15p-30=30+26p\\ 15p-30-26p=30\\ 15p-26p=30+30\\ -11p=30+30\\ -11p=60\\ \\p=-\frac{60}{11}=-5\frac{5}{11}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
ответ:
[tex]\displaystyle 1)\frac{27}{2}=13\frac{1}{2}=13,5\\ \\2)-\frac{60}{11}=-5\frac{5}{11}[/tex]
решение:
[tex]\displaystyle 1)-6(2x+7)+3(5x-9)=12-3x\\-12x-42+3(5x-9)=12-3x\\-12x-42+15x-27=12-3x\\3x-42-27=12-3x\\3x-69=12-3x\\3x-69+3x=12\\3x+3x=12+69\\6x=12+69\\6x=81\\\\x=\frac{27}{2}=13\frac{1}{2}=13,5\\[/tex]
[tex]\displaystyle 2)2\frac{1}{4}(\frac{2}{3}p-1\frac{1}{3})=3+2\frac{3}{5}p\\ \\\frac{9}{4}(\frac{2}{3}p-1\frac{1}{3})=3+2\frac{3}{5}p\\ \\\frac{9}{4}(\frac{2}{3}p-\frac{4}{3})=3+2\frac{3}{5}p\\ \\\frac{9}{4}(\frac{2}{3}p-\frac{4}{3})=3+\frac{13}5}p\\ \\\frac{3}{2}p-3=3+\frac{13}{5}p\\ \\15p-30=30+26p\\ 15p-30-26p=30\\ 15p-26p=30+30\\ -11p=30+30\\ -11p=60\\ \\p=-\frac{60}{11}=-5\frac{5}{11}[/tex]